2014
DOI: 10.3109/1547691x.2014.914609
|View full text |Cite
|
Sign up to set email alerts
|

Acute high-level exposure to WTC particles alters expression of genes associated with oxidative stress and immune function in the lung

Abstract: First responders (FR) present at Ground Zero in the first 72 h after the World Trade Center (WTC) collapsed have progressively exhibited significant respiratory injuries. The few toxicology studies performed to date evaluated effects from just fine (<2.5 µm) WTC dusts; none examined health effects/toxicities from atmospheres bearing larger particle sizes, despite the fact the majority (496%) of dusts were >10µm and most FR likely entrained dusts by mouth breathing. Using a system that generated/delivered super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…This may be important in limiting inflammatory responses to WTC dust. Our findings that WTC dust induces oxidative stress are in accord with a recent report in a rat model of inhalation exposure (Cohen et al, 2015). We also found that numbers of neutrophils in BAL were increased at 7 d and 21 d after exposure of mice to WTC dust.…”
Section: Discussionsupporting
confidence: 93%
“…This may be important in limiting inflammatory responses to WTC dust. Our findings that WTC dust induces oxidative stress are in accord with a recent report in a rat model of inhalation exposure (Cohen et al, 2015). We also found that numbers of neutrophils in BAL were increased at 7 d and 21 d after exposure of mice to WTC dust.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that WTC dust induces oxidative stress [5,6]. Consistent with these reports, tissue samples from all patients examined were found to stain positively for the oxidative stress markers, HO-1 and Lcn-2.…”
Section: Discussionsupporting
confidence: 85%
“…Spontaneously hypertensive rats (SHR) were exposed to the WTC dust or isoflurane (ISO) anesthesia alone in an intratracheal inhalation integrated system as described previously (12,13). Sets of rats were exposed to WTC53 dust at 33 mg dust/m 3 under ISO anesthesia for 2 hours/day on two consecutive days.…”
Section: Rna-seq Of Rat Prostate Exposed To Wtc Dustmentioning
confidence: 99%